Designing the careful and kind clinic: an evidence-based approach. Issue 2 (15th December 2021) - Poplau, Sara; Linzer, Mark; Allwood, Dominique; Montori, Victor; Armbruster, Ryan; Koka, Sreenivas
Abstract : Background: There is evidence that creating a 'healthy workplace' can be of profound importance for clinicians, team members and patients. Yet there have been few papers that have proposed mechanisms to take decades of research and translate this into a practical list of options for leaders and managers to take into account when structuring a clinic based on care and kindness to achieve optimal health. Evidence: We bring together 20 years of scholarship linking care of the caregivers with outcomes for caregivers and patients. The data are used to support both structures and cultures that will result in satisfied and thriving healthcare team members, as well as satisfied and healthy patients. Results: The clinic based on care of the caregivers will be structured to address key aspects of worklife that are known to cause either satisfaction or burnout. Aspects of care, such as time pressure, chaotic environments and worker control of their workplace, will be taken into account in clinical design; organisational culture will be supportive and cohesive, emphasising quality, values and communication. Experiences based on gender and race will be measured and continuously improved; and performance will be evaluated in a new, human-centred manner. Outcomes: The careful and kind clinic will be a remarkable place to work; in contrast to industrialised healthcare, this will be an environment where health can indeed be optimised, for both workers and patients.